Teachers’ Experiences With Online Teaching During COVID-19 in Kenya and Namibia - Elizabeth Ndeukumwa Ngololo; Haaveshe Nekongo-Nielsen; John Odhiambo (Indonesia Approach Education, 2023)
During the COVID-19 pandemic across sub-Saharan Africa, the sudden closure of schools has interrupted and brought physical learning to a standstill. The rapid transition to emergency remote teaching posed many challenges and required innovative approaches to ensure continuity of teaching through information technology tools in Kenya and Namibia. Online Collaborative Learning (OCL) theory supports an effective teaching strategy for teachers to adopt appropriate technologies and clear educational goals, develop clear instructions for influencing students’ online behavior, prepare and orientate students adequately, and select pertinent discussion topics. The study used a cross-sectional survey of secondary school teachers in both countries. The results show that teachers continued to provide education during the pandemic without proper guidance from the school leadership. Teachers lacked knowledge and support in developing appropriate online content, motivating students, and delivering quality teaching. Also, the results show no evidence-based online collaborative learning among teachers and/or schools. Similarly, schools lacked knowledge practices and digital resources, especially those in rural settings. The study recommends the improvement of continuing professional development in the respective countries, covering aspects of the school vision, leadership, practices of the teaching community, pedagogical approaches, school-level knowledge practices, and increased digital resources.